2012
DOI: 10.1111/j.1440-1746.2012.07283.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for pancreatitis and cholecystitis in endoscopic covered metal stenting for distal malignant biliary obstruction

Abstract: Non-pancreatic cancer and contrast injection into the pancreatic duct were predictive factors for pancreatitis, and tumor involvement to the OCD was a positive predictive factor for cholecystitis after endoscopic covered SEMS placement for distal malignant biliary obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(64 citation statements)
references
References 23 publications
2
59
3
Order By: Relevance
“…Placement of SEMSs with a high AF has been reported to be significantly related to the development of pancreatitis, stent patency, and cholecystitis 16-19. We measured the AF and RF of m-CZSs using methods described previously 5.…”
Section: Discussionmentioning
confidence: 99%
“…Placement of SEMSs with a high AF has been reported to be significantly related to the development of pancreatitis, stent patency, and cholecystitis 16-19. We measured the AF and RF of m-CZSs using methods described previously 5.…”
Section: Discussionmentioning
confidence: 99%
“…There is a subset of patients who survive much longer than this (up to 26 months). Previous work has suggested that use of contrast and a non-pancreatic cancer increase the risk of procedural complications 4. Similarly, longer term stent patency is associated with tumours <30 mm,5 or lower stage malignancy 6.…”
Section: Discussionmentioning
confidence: 99%
“…Despite these data, concern remains over potentially increased pancreatitis with use of fully covered metal stents. A small retrospective series reported that nonpancreatic cancer and injection of the pancreatic duct were risk factors for pancreatitis in patients with partially and fully covered metal stents placed [10]. The strength or osmolarity of the contrast plays no significant role in increasing the risk of pancreatitis.…”
Section: Procedure-related Risk Factorsmentioning
confidence: 96%